Developing and Assessing the Effectiveness of a Nurse-Led Home-Based Educational Programme for Managing Breathlessness in Lung Cancer Patients. A Feasibility Study - Aristides Choratas; Evridiki Papastavrou; Andreas Charalambous; Christiana Kouta (FRONTIERS MEDIA SA, 2022)
Introduction:Breathlessness is the most common and refractory symptom in lung cancer patients. Even though various educational programmes have been developed, only a few were intended for implementation in the home setting for its management.
Aim:Feasibility of a study for implementing a nurse-led educational programme for breathlessness management of lung cancer patients at home.
Method:A randomized feasibility study was undertaken between February 2017 and October 2018. Patients were recruited through referral from oncologists from two oncology centers in Cyprus under certain inclusion and exclusion criteria. Patients were randomized in the intervention or control group via a computer programme, and their named family caregivers (f.c.) were allocated in the same group. Participants were not blinded to group assignment. The intervention consisted of a PowerPoint presentation and implementation of three non-pharmacological interventions. The control group received usual care. Patients were assessed for breathlessness, anxiety, and depression levels, whereas f.c. were assessed for anxiety, depression, and burden levels. F.c. also assessed patients' dyspnea level. The duration of the study process for both the intervention and control group was over a period of 4 weeks. Results:Twenty-four patients and their f.c. (n= 24) were allocated equally in the intervention and control group. Five patients withdrew, and the final sample entered analysis was 19 patients and 19 family caregivers. In the intervention groupn= 11 + 11, and in the control groupn= 8 + 8. In the intervention group patients' breathlessness and anxiety levels showed improvement and their f.c.s in the anxiety and burden levels. Major consideration was the sample size and the recruitment of the patients by the referring oncologists. Attrition was minor during the study process. No harm was recorded by the participants of the study.
Conclusions:The study provided evidence of the feasibility of the implementation of the educational programme. For the future definitive study major consideration should be patients' recruitment method in order to achieve adequate sample size. Moreover, qualitative data should be collected in relation to the intervention and the involvement of f.c. The feasibility study was registered to the Cyprus Bioethics Committee with the registration number 2016/16. There was no funding of the study.